Tunable‐Emission Amorphous Room‐Temperature Phosphorescent Polymers Based on Thermoreversible Dynamic Covalent Bonds. (14th December 2020) - Lin, Xiaohan; Wang, Jie; Ding, Bingbing; Ma, Xiang; Tian, He
Abstract: Pure organic room‐temperature phosphorescence (RTP) materials are useful for photoelectric, biochemical devices, and bioimaging sensors. In the last few years, dynamic covalent chemistry has aroused substantial attention as it offers a way to create intelligent materials with feedback and response functions. Through a Diels–Alder reaction, a [4+2] cycloaddition reaction between dienes and dienophiles, three polymers were synthesized that can be reversibly transformed by thermally reversible dynamic covalent bonds. All polymers show decent RTP emission with different colors. For the poly‐Br‐An solid, the absolute phosphorescence quantum yield reaches up to 12 %. This study provides a new method for the rational design and synthesis of tunable‐emission organic RTP materials via dynamic covalent bonds. Abstract : We developed a facile approach to realizing efficient room‐temperature phosphorescence (RTP) in the amorphous state. Tunable emission has been achieved by introducing a thermoreversible dynamic covalent bond into pure organic room‐temperature phosphorescence polymers. This innovative strategy may expand the application range of intelligent materials.